The olfactory behaviour of spotted hyaenas (Crocuta crocuta) and sympatric mammals in the Okavango Delta, Botswana - Vitale, Jessica (2018)
Understanding the natural behaviour and coexistence of species is important for the conservation of intact ecosystems, and behavioural studies can enhance our knowledge of processes such as communication and competition. I investigated the social dynamics and scent-marking behaviour of spotted hyaenas (Crocuta crocuta), and the occurrence of interspecific olfactory eavesdropping among African mammals, within the Okavango Delta ecosystem of Botswana. First, social network analysis found that the hyaena population was comprised of five main clans that maintained territories but whose home ranges overlapped considerably. Scavenging at large carcasses involved associations between individuals from different clans and resulted in relative tolerance toward territorial intruders. Second, observations of communal latrine use found that latrines are likely involved in territorial advertisement by hyaena clans, and cyclical patterns of latrine growth and decline were linked to annual rainfall. Third, a translocation experiment showed that hyaena scats appear to be less important for hyaena communication than other cues associated with latrines, especially as hyaenas did not differ in their behaviour towards scat originating from latrines located in resident versus non-resident clan home ranges. Heterospecific mammals investigated, scent-marked, and were vigilant at hyaena latrines, suggesting a potential function for hyaena latrines in interspecific eavesdropping and/or communication. Fourth, a urine presentation experiment found that the investigation of sympatric predator urine by African mammals stimulated vigilance behaviour, suggesting that olfactory signals provide information about predation risk. Hyaenas exhibited context-specific differences in behaviour towards predator urine: they were more likely to investigate urine samples alongside indicators of predator activity (i.e. carrion odour, carcasses) and were most likely to exhibit vigilance at carcasses when exposed to urine from lions and wild dogs. This study greatly enhanced our understanding of spotted hyaena behaviour within the Okavango Delta, an important ecosystem for the conservation of African large predators. Furthermore, this study provided the first experimental evidence of the role of hyaena scats in intraspecific communication and interspecific olfactory eavesdropping at latrines. My research findings regarding the population’s clan structure and home ranges will form the foundation for subsequent investigation into human-wildlife conflict in the study area. Furthermore, the results from two scent experiments shed light on the potential importance of olfactory signals for mediating interspecific interactions among African mammals, particularly among large predators.